“Scalds of America”. Bayard Taylor and Samuel Kneeland in the Millennium of the Colonisation of Iceland (1874) - Mossé, Marie (Viatica, 2017)
International audience In the Romantic period, Travel mixed writing about elsewhere with writing about oneself. The naturalist Samuel Kneeland and the poet and journalist Bayard Taylor, travelling to Iceland in 1874, took advantage of this new plasticity offered by travel writing. The two Americans composed a unique literary relationship in which scholarly discourse faded away to give way to an imaginative relationship with reality. À l’âge romantique, le Voyage mêle écriture de l’ailleurs et écriture de soi. Le naturaliste Samuel Kneeland et le poète et journaliste Bayard Taylor, voyageant en Islande en 1874, profitent de cette nouvelle plasticité offerte par l’écriture viatique. Les deux Américains composent une relation littéraire originale au sein de laquelle le discours savant s’efface pour laisser place à un rapport imaginatif au réel.